Analysis of disease perceptions and islamic sharia values of interest in using voluntary counseling and testing services in Langsa City Aceh Province - Diza Fathamira Hamzah; Teuku Chik Mohamed Iqbal Fauriza; M Rizal (Jurnal SAGO Gizi dan Kesehatan, 2025)
Background: HIV/AIDS remains a significant global health issue, prompting community meetings to promote Voluntary Counseling and Testing (VCT) clinics in Langsa City.Objectives: This study aimed to analyze the perceptions of illness and Islamic Sharia values regarding interest in using VCT services.Methods: This study was a mix-method approach with concurrenct triangulation in Bungoeng Tulip VCT Clinic, Langsa City Regional Hospital.  This six-months involved 42 participants, including health workers and religious leaders. Data were collected through in-depth interviews and analyzed using both quantitative and qualitative methods used content analysis techniques.Result: The results showed that Informants' view of threat and severity of the disease have an impact on their interest in using VCT services. Additionally, mass media and health worker promotions significantly influence user participation in VCT. However, perceptions of disease severity and islamic values did not affect informant decisions to utilize these services in Langsa.Conclusion: Most respondents had a positive perception of the disease and Islamic values concerning VCT services. Nonetheless, perception of disease severity and Islamic law did not significantly influence the utilization of VCT clinic. It is recommended to develop and promote targeted health education initiatives that focus on awareness of disease severity and the importance of utilizing VCT services.